(untitled) (Malay Literature, 2022)
Generally, the production of historical novels demands the author to adhere to accuracy of facts in the effort to convey his story. However, as a literary work, elements related to creativity and authorship are inevitable to ensure that the work produced is able to attract the attention of readers. Indeed, every author possesses their own creativity and authorship in producing historical novels. Therefore, this study is a comparative analysis of creativity and authorship in the historical novels of Affifudin Omar from Malaysia and Langit Kresna Hariadi from Indonesia. The historical novels selected for this study are Tun Perak Paduka Raja (2017) and Gajah Mada Makar Dharmaputra (2012). This study employs Kristeva’s (1980) principles of intertextuality to assess the writers’ creativity and authorship in transmuting traditional literary texts into historical novels. This will highlight the strengths and weaknesses of the two authors. This study is significant in that it reveals the dynamics of thinking of writers of historical novels from the Malay Archipelago. Full text: PDF